PENGARUH KEPRIBADIAN DAN EFEKTIVITAS TIM TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI DI BADAN PENDIDIKAN DAN PELATIHAN KEMENTERIAN DALAM NEGERI - Yarouf Estianda (Jurnal Manajemen Pendidikan, 2014)
The objective of this research is to understand comprehensively the effect of personality and team effectiveness toward Organizational Citizenship Behaviour (OCB) of the civil servant in Education and Training Agency of The Ministry of Home Affairs. The research used a survey method with path analysis applied in testing hyphotesis. It was conducted to 128 civil servants as the respondents which were selected in a simple random way. The data analysis and interpretation reveals that (1) personality has direct positive influence toward OCB, (2) team effectiveness has direct positive influence toward OCB, (3) personality has direct positive influence toward team effectiveness.